2005
DOI: 10.1128/iai.73.5.2974-2985.2005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Strain-Transcending Immunity againstPlasmodium chabaudi adamiMalaria with a Multiepitope DNA Vaccine

Abstract: A major goal of current malaria vaccine programs is to develop multivalent vaccines that will protect humans against the many heterologous malaria strains that circulate in endemic areas. We describe a multiepitope DNA vaccine, derived from a genomic Plasmodium chabaudi adami DS DNA expression library of 30,000 plasmids, which induces strain-transcending immunity in mice against challenge with P. c. adami DK. Segregation of this library and DNA sequence analysis identified vaccine subpools encoding open readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Apart from ADCI, opsonising antibodies enhance the phagocytosis and elimination of infected red blood cells by macrophages in vitro and are induced by vaccines protecting BALB/c mice against P.c. adami infection (46, 47). The potential regulatory role for MIF on IL-4 responses in granulocytes, on Th2 sketching and on protection in malaria is interesting as these cells, centrally involved in the acute inflammatory reactions to allergens, are now being considered general inducers of Th2 responses (34).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from ADCI, opsonising antibodies enhance the phagocytosis and elimination of infected red blood cells by macrophages in vitro and are induced by vaccines protecting BALB/c mice against P.c. adami infection (46, 47). The potential regulatory role for MIF on IL-4 responses in granulocytes, on Th2 sketching and on protection in malaria is interesting as these cells, centrally involved in the acute inflammatory reactions to allergens, are now being considered general inducers of Th2 responses (34).…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that the same principle can be applied to DNA vaccines by producing epitope vaccines against Eimeria infections. Scorza et al (2005) described a multi-epitope malaria vaccine and showed that the vaccine conferred protection against a heterologous parasite infection in BALB/c mice studies (Scorza et al, 2005). Similarly, Tian et al (2008) showed that a multi-epitope DNA vaccination led to a dramatic augmentation of humoral and cellular responses, and provided up to an 80% immune protection against infectious bronchitis virus (IBV) (Tian et al, 2008).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Procedures for Plasmodium chabaudi adami animal experiments were approved by the Macdonald Campus Animal Care Committee of McGill University, and procedures for Plasmodium berghei animal experiments were approved by the New York University School of Medicine Institutional Animal Care and Use Committee. Groups of female BALB/c mice (18 -20 g) were injected intraperitoneally (ip) on day 0 with rodent malarial parasites from an infected donor mouse [14]. Mice were infected with 0.5 ϫ 10 5 -1 ϫ 10 5 parasites.…”
Section: Methodsmentioning
confidence: 99%
“…Parasitemia was monitored from thin blood films, as described elsewhere [9]. The total parasite burden per mouse was calculated from the cumulative parasitemia throughout the trial [14,15]. A 4-day suppression test was used, as described elsewhere [16].…”
Section: Methodsmentioning
confidence: 99%